Will a mAb-Based Immunotherapy Directed against Cancer Stem Cells Be Feasible? - Santamaria, Silvia; Delgado, Marisa; Kremer, Leonor; Garcia-Sanz, Jose A. (Frontiers in Immunology, 2017)
The Cancer Stem Cell (CSC) hypothesis suggests that within a tumor, there is a small subpopulation of cells with stem cell properties responsible for tumor maintenance and metastasis generation. This hypothesis also implies that new anti-tumor drugs, rather than targeting the bulk of the tumor mass, would be more effective if they directly targeted the CSC subpopulation. The CSCs from several types of tumors have been identified with mAbs recognizing surface antigens in these cells; however, antigens specifically or exclusively expressed in the CSC population have not yet been identified. Thus, questioning the possibility of using therapeutic antibodies directed against the CSCs. Here we review the possibilities of using antibodies directly targeting the CSCs as therapeutic agents either in the form of naked antibodies, antibodies conjugated to nanoparticles or antibody cocktails.